2019
DOI: 10.1111/jace.16819
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dopant precursors on the optical properties of rare‐earths doped oxyfluoride glass‐ceramics

Abstract: The crystallization of fluoride nanocrystals (NCs) in chemically and mechanically stable aluminosilicate glasses has shown interesting optical properties even for small crystal fractions (10‐15 wt%). When rare‐earth (RE) ions are used as dopants, crystal‐like features can be reproduced and an increase in the emission and/or energy transfer processes, with respect to the starting glasses, is observed. A crucial point for these materials is the study of the local surrounding of RE ions and their incorporation in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Various glass oxyfluoride systems are also important for optical and photonic applications, , including glass ceramics with F-containing optically active crystals and rare-earth fluoride-containing systems for lasers . Of the oxyfluoride glass-forming systems that have been investigated, including silicate and borate systems, perhaps the most important for optics has been fluoride-containing phosphate glasses. , …”
Section: Introductionmentioning
confidence: 99%
“…Various glass oxyfluoride systems are also important for optical and photonic applications, , including glass ceramics with F-containing optically active crystals and rare-earth fluoride-containing systems for lasers . Of the oxyfluoride glass-forming systems that have been investigated, including silicate and borate systems, perhaps the most important for optics has been fluoride-containing phosphate glasses. , …”
Section: Introductionmentioning
confidence: 99%
“…It is found that most of the RE ions are concentrated in the uorine-rich amorphous regions in the parent glass, and the crystallization process triggers the redistribution and incorporation of RE ions in uoride nanocrystals. 31 Herein, a novel Tb 3+ doped uorosilicate glass is synthesized by melt-quenching method, and KTb 2 F 7 nanocrystals are precipitated from the glass via the subsequent heat-treatment. The microstructure and optical properties of GC containing KTb 2 F 7 nanocrystals are investigated by X-ray diffraction (XRD) patterns, transmission electron microscopy (TEM) images, transmission spectra, photoluminescence spectra, Raman spectra and FTIR spectra.…”
Section: Introductionmentioning
confidence: 99%
“…It is found that most of the RE ions are concentrated in the fluorine-rich amorphous regions in the parent glass, and the crystallization process triggers the redistribution and incorporation of RE ions in fluoride nanocrystals. 31…”
Section: Introductionmentioning
confidence: 99%